Pengembangan Lms Berbasis Problem Based Learning Untuk Meningkatkan Keterampilan Berpikir Kritis Murid Pada Pemrograman Terstruktur - Kayla Syva Syahputri; Atan Pramana (CV. SINAR HOWUHOWU, 2026)
Twenty-first-century learning requires students to develop critical thinking skills to solve programming problems. Observations conducted in Grade X of the Software Engineering program at SMK Negeri 2 Surabaya revealed that Structured Programming instruction remains teacher-centered and is not supported by interactive learning media. This study aimed to examine the feasibility and effectiveness of a Problem-Based Learning (PBL)-based Learning Management System (LMS) in improving students' critical thinking skills. This study employed a Research and Development (R&D) approach using the ADDIE model. The research involved an experimental class and a control class using a Non-Equivalent Control Group Design. Data were collected through expert validation, black-box testing, observation, documentation, and pretest-posttest assessments, and analyzed using feasibility percentages and the Mann-Whitney U test The results showed that the developed LMS was feasible for classroom use, with expert validation scores of 90.47% for software engineering, 90.00% for learning materials, 91.25% for learning assessment, and 81.00% for instructional design. Black-box testing confirmed that all system features functioned properly. Furthermore, the PBL-based LMS improved students' critical thinking skills, as indicated by the higher mean posttest score of the experimental class (85.88) compared with the control class (75.69) (p < 0.001). These findings imply that the developed PBL-based LMS can serve as an alternative digital learning medium for Structured Programming and provide teachers with a practical reference for designing student-centered learning that supports the development of students' critical thinking skills.